Social learning in situations of complexity: guidelines for fostering Communities of Practice - Bailey, Arwen; Elias, Marlène; Victor, Michael; Maru, Joyce; Nicol, Alan (2022)
One way that actors can share experiences and knowledge about what works for a collective goal is through engaging in Communities of Practice. A Community of Practice, or CoP, has been defined as “a gathering of individuals motivated by the desire to cross organizational boundaries, to relate to one another, and to build a body of actionable knowledge through coordination and collaboration” (World Bank Group, 2021). While much has been written about CoPs for the private sector and in sectors such as health, there is a gap in guidance on how to establish and sustain them for sustainable development in agriculture and natural resource management. This publication helps fill that gap.